A Policy Review of the Tourism Ecosystem Paradigm in Indonesia's Law No. 18/2025 - Bintari Pangesti Putri; Mega Fitriani Adiwarna Prawira; Rumba (Politeknik Negeri Bandung, 2026)
Indonesia's Law No. 18/2025 marks a decisive shift from a quantity-driven framework to a quality-focused